Management of Soft Tissue Injuries Associated with Tibial Plateau Fractures - Borrelli, Joseph, Jr. (The Journal of Knee Surgery, 2014)
Tibial plateau fractures or knee fracture–dislocations often result from trauma or sporting injuries. Given the subcutaneous position of the knee and upper tibia, without much intervening soft tissue, any such injury can be associated with significant soft tissue damage. Thus, consideration of the degree of soft tissue injury must be part of the treatment plan. Specific management decisions regarding blisters, open wounds, and compartment syndrome are discussed, as well as the timing of surgery, role of provisional external fixation, and placement of incisions for definitive internal fixation.
Keywords: tibial plateau fracture; soft tissue injury; fracture blister